Natural human rights : a theory - Boylan, Michael
Part I. Conceptualizing Human Rights: 1. How do we talk about human rights? 2. A short history of human rights in the West 3. Human rights in China Part II. Justifications for Human Rights: 4. Legal justifications 5. Interest justifications 6. Agency justifications 7. Ontology, justice, and human rights Part III. Applications of Human Rights: 8. War rape 9. Political speech 10. LGBT rights.